Community-focused selective dissemination of information services for empowering women through information provision and utilization: center for learning resources as a catalyst for social change (2015)
With the rapidity of transformation of the modern society to a knowledge economy, as well as the ever increasing deployment of ICT for retrieval and management of knowledge by libraries, global solutions are now available for hitherto localized and seemingly intractable problems. As laudable as this scenario of a flat world which provides information for virtually any issue of human concern, in unimaginable dimension, may seem, there still exists the need to bridge the yawning gap in women’s information access and utilization in Nigeria. It is against this background that the study surveyed and show-cased practical outreach undertaken by the Centre for Learning Resources (Covenant University Library) in addressing particular information needs of women within its environs. The paper highlighted community impact initiatives, workshops, and research targeted at ameliorating specific deficiencies associated with women through the instrumentality of information access and library services. The study extrapolated from the unique experiences of the Centre for Learning Resources, Covenant University to construct a model for modern libraries in developing countries for evolving as agent of reconstruction of their immediate geo-polity. It identified constraints of libraries in community services. The paper concluded that libraries should traverse traditional roles to embrace challenges presented by their peculiar setting in order to maintain continuous relevance